Body composition as a predictor of physical performance in older age: A ten-year follow-up of the Helsinki Birth Cohort Study. (July 2018) - Mikkola, Tuija M.; von Bonsdorff, Mikaela B.; Salonen, Minna K.; Simonen, Mika; Pohjolainen, Pertti; Osmond, Clive; Perälä, Mia-Maria; Rantanen, Taina; Kajantie, Eero; Eriksson, Johan G.
Highlights: Greater adiposity predicted poorer physical performance ten years later. Measures of adiposity predicted physical performance better than those of lean mass. Lean mass was inversely associated with physical performance. Abstract: Background: This study assessed how different measures of body composition predict physical performance ten years later among older adults. Methods: The participants were 1076 men and women aged 57 to 70 years. Body mass index (BMI), waist circumference, and body composition (bioelectrical impedance analysis) were measured at baseline and physical performance (Senior Fitness Test) ten years later. Linear regression analyses were adjusted for age, education, smoking, duration of the follow-up and physical activity. Results: Greater BMI, waist circumference, fat mass, and percent body fat were associated with poorer physical performance in both sexes (standardized regression coefficient [β] from −0.32 to −0.40, p < 0.001). Lean mass to BMI ratio was positively associated with later physical performance (β = 0.31 in men, β = 0.30 in women, p < 0.001). Fat-free mass index (lean mass/height 2 ) in both sexes and lean mass in women were negatively associated with later physical performance. Lean mass residual after accounting for the effect of height and fat mass was not associated with physical performance. Conclusions: Among older adults, higher measures of adiposity predicted poorer physical performance ten years later whereas lean mass was associated with physical performance in a counterintuitive manner. The results can be used when appraising usefulness of body composition indicators for definition of sarcopenic obesity.